Noncoding RNAs: key molecules in understanding and treating pain - Bali, Kiran Kumar; Kuner, Rohini (Trends in molecular medicine, 2014)
Although noncoding RNAs (ncRNAs) were initially considered to be transcriptional byproducts, recent technological advances have led to a steady increase in our understanding of their importance in gene regulation and disease pathogenesis. In keeping with these developments, pain research is also experiencing rapid growth in the investigation of links between ncRNAs and pathological pain. Although the initial focus was on analyzing expression and dysregulation of candidate miRNAs, elucidation of other ncRNAs and ncRNA-mediated functional mechanisms in pain modulation has just commenced. Here we review the major ncRNA literature available to date with respect to pain modulation and discuss tools and opportunities available for testing the impact of other types of ncRNA on pain.
Gesehen am 04.09.2020